Transforming Food Systems - Mosnier, Aline; Springmann, Marco; Fan, Shenggen; Campbell, Bruce; Harwatt, Hellen; Romero, Julia Rocha; Zhang, Wei (United Nations Environment Programme, 2022)
Food systems are major contributors to climate change and other environmental problems, such as land-use change and biodiversity loss, depletion of freshwater resources, and pollution of aquatic and terrestrial ecosystems through nitrogen and phosphorus run-off from fertilizer and manure application (Cordell and White 2014; Crippa et al. 2021; Diaz and Rosenberg 2008; Foley et al. 2005; Newbold et al. 2015; Robertson and Vitousek 2009; Shiklomanov and Rodda 2004; Intergovernmental Panel on Climate Change [IPCC] 2019; Wada et al. 2010; Willett et al. 2019).